The Film “Ipar Aaalah Maut” as an Islamic Da'wah Media on The Phenomenon of Domestic Infidelity - Istighfarany, Annisa Ghina; Wardhani, Andy Corry; Aryanti, Nina Yudha; Kartika, Tina (IJESS International Journal of Education and Social Science, 2025)
Marital infidelity is one of the main causes of the increasing divorce rate in Indonesia. Despite being a religious society, the high number of cases of marital betrayal in Indonesia indicates a moral crisis and a weakening awareness of Islamic values. This study uses Stuart Hall's approach to media representation to analyse the film Ipar Adalah Maut as an Islamic da'wah medium representing the problem of infidelity, in relation to the da'wah communication concepts of bil hal, bil hikmah and bil lisan. A descriptive qualitative approach was used, with data collected through documentation, a literature study and non-participatory observation. Qualitative analysis was conducted using semiotic and interpretative approaches. The results showed that the film conveys moral and religious messages through three representational strategies: reflective, intentional and constructionist. The scenes convey da'wah messages symbolically and emotionally, illustrating the destructive impact of infidelity and the importance of maintaining social boundaries in Islam. Da'wah bil hal is exemplified by an Islamic family, da'wah bil hikmah by a moving storyline, and da'wah bil lisan by the dialogue and prayers of the protagonist. Overall, this film successfully conveys Islamic da'wah values in a contextual manner, establishing it as a relevant and effective modern medium for da'wah communication.